Phytotoxic, insecticidal, and antimicrobial activities of Ajania tibetica essential oil - Han, Caixia; Zhou, Shixing; Mei, Yu; Cao, Qiumei; Shi, Kai; Shao, Hua (Frontiers in Plant Science, 2022)
The chemical profile of Ajania tibetica essential oil (EO) and its phytotoxic, insecticidal, and antimicrobial activities were assessed. Monoterpenes (79.05%) and sesquiterpenes (10.33%) were dominant in the EO, with camphor, (+/-)-lavandulol and eucalyptol being the major constituents, representing 55.06% of the total EO. The EO possessed potent phytotoxicity against Poa annua and Medicago sativa starting from 0.5 mg/mL, and when the concentration rose to 5 mg/mL, seed germination of both tested species was 100% suppressed. Ajania tibetica EO displayed significant pesticidal activity against Aphis gossypii with an LC50 value of 17.41 μg/mL; meanwhile, the EO also showed antimicrobial activity against Escherichia coli, Bacillus subtilis, Verticillium dahlia and Aspergillus niger using broth microdilution and disc diffusion methods. For the tested bacterial and fungal strains, the EO exhibited a repressing effect, with minimum inhibitory concentrations (MICs) ranging from 0.3125 to 1.25 mg/mL for bacteria and from 1.25 to 2.5 mg/mL for fungi, whereas the minimum microbicidal concentrations (MMCs) were 5 mg/mL for bacteria and 2.5 mg/mL for fungi. Our study is the first report on the chemical profile as well as the phytotoxicity, insecticidal and antimicrobic activity of A. tibetica EO, indicating its potential value as an alternative synthetic pesticide.